KORELASI PEENERAPAN PAIKEM TERHADAP HASIL BELAJAR PESERTA DIDIK PADA SMA ISLAM AL-AZHAR 12 MAKASSAR - Al Bazzar Al Bazzar (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Creating a student-oriented and enjoyable teaching and learning process is the task of all teachers and educators. The presence of various learning methods and strategies is inseparable from the participation of researchers who continue to strive to present learning activities that are active, creative and fun. One of them is the application of PAIKEM in the teaching and learning process in the classroom, although not all classes benefit from this method, it takes in-depth and measurable observation to find out. This study aims to determine the implementation of PAIKEM learning at Al-Azhar 12 Islamic High School Makassar and student learning outcomes with the application of PAIKEM. In addition, researchers also analyzed the level of correlation between PAIKEM learning and student learning outcomes at SMA Islam Al-Azhar 12 Makassar. This research is an ex post facto research with a quantitative approach. The population of this study were all students at SMA Islam Al-Azhar 12 Makassar. Sampling was carried out by proportional sampling and selected class X and class XI as research samples with the independent variable being PAIKEM learning and the dependent variable being the results of learning Al-Quran education for Al-Azhar 12 Islamic High School Makassar students. Hypothesis testing was carried out with the Excel program using descriptive and inferential statistical analysis (product moment simple regression correlation). The results showed that: (1) the implementation of PAIKEM learning at Al-Azhar 12 Islamic High School Makassar was classified as good with an average score of PAIKEM learning outcomes of 80.27. (2) student learning outcomes at AMA Islam Al-Azhar 12 Makassar are in the good category with an average student learning outcome of 79.96. (3) PAIKEM learning is significantly correlated with student learning outcomes in Al-Azhar 12 Islamic High School Makassar with rcount 0.9 > rtable 0.294 and the strength of the relationship between PAIKEM learning and learning outcomes is 81%. With these results, of course, it will be a guide for teachers and future researchers, especially in the field of education